2014
DOI: 10.1089/ten.tea.2013.0694
|View full text |Cite
|
Sign up to set email alerts
|

Passive Strain-Induced Matrix Synthesis and Organization in Shape-Specific, Cartilaginous Neotissues

Abstract: Tissue-engineered musculoskeletal soft tissues typically lack the appropriate mechanical robustness of their native counterparts, hindering their clinical applicability. With structure and function being intimately linked, efforts to capture the anatomical shape and matrix organization of native tissues are imperative to engineer functionally robust and anisotropic tissues capable of withstanding the biomechanically complex in vivo joint environment. The present study sought to tailor the use of passive axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 75 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…6). Dynamic loading during in vitro culture has been shown to promote collagen alignment that mimics the structural and functional properties of the native tissue [74, 75], and could ameliorate the lack of organization observed in the current study. Together, these findings demonstrated that the decellularized CDM retained its chondroinductive capacity and ability to prevent a hypertrophic phenotype in MSCs; however, further work is needed to achieve hierarchical organization of the newly synthesized tissue.…”
Section: Discussionmentioning
confidence: 99%
“…6). Dynamic loading during in vitro culture has been shown to promote collagen alignment that mimics the structural and functional properties of the native tissue [74, 75], and could ameliorate the lack of organization observed in the current study. Together, these findings demonstrated that the decellularized CDM retained its chondroinductive capacity and ability to prevent a hypertrophic phenotype in MSCs; however, further work is needed to achieve hierarchical organization of the newly synthesized tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrocartilage derived from meniscus and articular chondrocyte cocultures also yielded a 27% increase in collagen content when stimulated passively with a 0.1 N DC load. 72 Although collagen II content specifically needs to be investigated more thoroughly, these studies show that DC is a potent regimen for increasing total collagen content.…”
Section: Direct Compressionmentioning
confidence: 99%
“…Their implantation evidenced positive results. Significant improvement of regeneration was observed with the spatiotemporal gradient of functionalization [ 176 ]. Same approaches were developed to engineer human 3D-printed TMJ discs.…”
Section: 3d Regeneration Of Tmjmentioning
confidence: 99%